2016
DOI: 10.22495/cbv12i2art1
|View full text |Cite
|
Sign up to set email alerts
|

Board meeting and firm performance: Evidence from the Amman stock exchange

Abstract: This study examines the impact of board meeting frequency on the firm performance of the firms listed on the Amman Stock Exchange from industry and service sectors for the 2009-2013 period. The study controls for endogeneity and simultaneously problems using the dynamic panel technique of Generalized Method of Moments (GMM). The findings of the study suggest that a positive association between the frequency of corporate board meetings and firm performance. This suggests that through meetings, board members det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 25 publications
4
16
2
2
Order By: Relevance
“…These results are consistent with Karamanou & Vafeas (2005); Ntim & Osei (2011);Al-Daoud et al (2016) shows that a positive relationship between the frequency of meetings of the board of directors and the performance of the company. With more meetings demonstrating the ability of higher board of commissioners to monitor their involvement and larger discussions leads to better decisions, thereby improving performance.…”
Section: Resultssupporting
confidence: 89%
“…These results are consistent with Karamanou & Vafeas (2005); Ntim & Osei (2011);Al-Daoud et al (2016) shows that a positive relationship between the frequency of meetings of the board of directors and the performance of the company. With more meetings demonstrating the ability of higher board of commissioners to monitor their involvement and larger discussions leads to better decisions, thereby improving performance.…”
Section: Resultssupporting
confidence: 89%
“…Nonetheless, the number of board meetings showed a significant negative impact on firm performance. The outcome is opposed to that of Al-Daoud et al (2016), who revealed that if board meetings are frequent, numerous matters could be discussed and judged based on various opinions, thus improving the decision-making process that boosts the overall firm performance. Concerning the theory, the findings prove the assumption that a gender-responsive board will drive superior performance, as contended by the information and decision-making approach presumption (Gruenfeld et al, 1996), contrary to Yang et al (2019).…”
Section: Robustness Checksmentioning
confidence: 87%
“…Ntim and Osei (2011) found a positive and significant association of board meetings with respect to firm performance after investigating a sample of 169 companies from South African and concluded that as the frequency of meetings on the board increases it eventually tends to generate higher profits. Al Daoud et al (2016) and Arora and Sharma (2016) found significance with positive impact of board meeting on the corporate performance as more meetings generate more value for firms. Whereas, Palaniappan (2017) has found a contradictory result regarding firms performance.…”
Section: Literature Reviewmentioning
confidence: 91%